Seismic reflectivity, fracturing and stress field data from the FFC-1 exploratory geothermal project in SW Skåne, Sweden - Juhlin, Christopher; Erlström, Mikael; Lund, Björn; Rosberg, Jan Erik (Geothermics, 2022)
Enhanced geothermal systems (EGS) are a potential heat source in many parts of the world, even in locations where the temperature gradient is relatively low. We present here an integrated study of reflection seismic data, borehole logs and seismicity analysis performed in conjunction with a geothermal exploratory project operated by E.ON in Malmö, Sweden. In 2020, the pre-existing 2.1 km deep FFC-1 borehole through the sedimentary cover was deepened into the crystalline basement to about 3.1 km vertical depth. Combined interpretation of the reflection seismic data and geophysical wireline logs show that most of the reflectivity in the Precambrian basement is likely generated by lenses of mafic amphibolite embedded in a felsic gneissic matrix. The general structural bedding and foliation is gently dipping to sub-horizontal, similar to other locations in southwest Sweden. Fracture frequency is relatively high in the crystalline rock mass, with heavy fracturing in the uppermost part of the crystalline basement, obscuring a clear reflection from the top of the Precambrian. Highly fractured and hydraulically conductive intervals are also found between 2,562 and 2,695 m based on a temperature drop and the interpretation of the geophysical data. Open fractures, both natural and induced, have a clear N–S orientation, contrasting with the expected NW–SE direction based on the orientation of the Sorgenfrei-Tornquist Zone and earthquake fault plane solutions to the north. This difference may be partly explained by local variations in the stress field near the FFC-1 borehole and vairations in the stress field with depth. Despite this, the data from the FFC-1 well provide novel and unique information on the complex physical state of the crystalline basement on the margin of the Fennoscandian Shield, which further addresses the need for obtaining in-situ stress data to fully understand the local stress field prior to any stimulation. A temperature of 84°C measured at 3 km depth indicates that a desired EGS temperature of ...